Bisphosphonate related osteonecrosis of the jaws: An update - Kumar, R Anil; Sawhney, Chand; Kumar, Santosh; Dhingra, Mohita (European Journal of General Dentistry, 2012)
Bisphosphonates (BPs) have been recommended for the use in patients with various bony lesions such as Paget′s disease, hypercalcemia, osteoporosis, and multiple myeloma. Despite the increasing use and various benefits, bisphosphonate related osteonecrosis of the jaw (BRONJ) is a significant complication with significant morbidity. A search of PUBMED journal databases from January 2000 to April 2012 was conducted with the objective of identifying publications regarding BRONJ. Based on the available data current concepts in the diagnosis and management of BRONJ are discussed in this article.
Keywords: Bisphosphonates; jaw; osteonecrosis